Penerapan QR Code Sebagai Media Akses Informasi Sejarah Pahlawan - Dirgantara, Andy Dwiputra; Riyadh, Achyar; Chrislianti, Reynita Mikhaela (Yayasan Petra Harapan Bangsa, 2017)
The hero who is immortalized as a street name is someone who has great historical and service value for the advancement of a country. Unfortunately in the city of Bandung people mostly do not know the historical background of the struggle and services that have been done by the hero. This study aims to find innovations that facilitate the public in obtaining information about historical stories from the heroes by utilizing technological advances. The research uses the product development flow with the method of design thinking, which aims to produce design solutions that match the characteristics of users. The research flow begins with the determination of design goals and target users, supporting data collection and defining the design criteria, finished by development of creative ideas and the making of prototypes. The study yielded a conclusion about the size and appearance used for the QR code signage board. The signage is located on the sidewalk area, adjacent to the street signboard, and is capable of being used at an ideal distance of 1-4 meters. This study also developed an interface for QR code scanner apps to facilitate users in accessing data about the historical struggle and service of the hero.Pahlawan yang diabadikan sebagai nama jalan adalah seseorang yang memiliki nilai sejarah dan jasa besar bagi kemajuan negara. Sayangnya di kota Bandung sebagian besar masyarakat tidak mengetahui latar belakang perjuangan dan jasa yang telah dilakukan oleh pahlawan tersebut. Penelitian ini bertujuan untuk menemukan inovasi yang memudahkan masyarakat dalam mendapatkan informasi mengenai cerita sejarah perjuangan dan jasa pahlawan dengan memanfaatkan kemajuan teknologi. Penelitian menggunakan alur pengembangan produk dengan metode design thinking, yang bertujuan untuk menghasilkan solusi desain yang sesuai dengan karakteristik pengguna. Alur penelitian diawali dengan penentuan tujuan perancangan dan khalayak pengguna, pengumpulan data pendukung dan kriteria perancangan, pengembangan gagasan kreatif dan pembuatan purwarupa. Penelitian menghasilkan simpulan mengenai ukuran dan tampilan yang digunakan pada papan signage QR code. Signage ini diletakan di area trotoar, berdekatan dengan papan nama jalan, dan mampu digunakan pada jarak ideal 1-4 meter. Penelitian ini juga mengembangkan tampilan antarmuka untuk aplikasi pemindai QR code agar memudahkan pengguna dalam mengakses data mengenai sejarah dan jasa pahlawan.